Fermented Chive (Allium schoenoprasum) with Lactobacillus plantarum: A Potential Antibiotic Alternative Feed Additive for Broilers Challenged with Escherichia coli - Phan Vu Hai; Le Xuan Anh; Nguyen Xuan Hoa (Fermentation)
This study aimed to evaluate the effects of fermented chive (Allium schoenoprasum) with Lactobacillus plantarum 1582 (FC) as an alternative to antibiotics for controlling Escherichia coli infection in broiler chickens. A total of 250 J-Dabaco male chickens were allocated into five experimental groups: NC (negative control), PC (positive control), FC1 (1% FC), FC3 (3% FC), and AB (antibiotic treatment). The PC, FC1, FC3, and AB groups were challenged with E. coli ExPEC_A338 on day 8 and monitored until day 35. The results indicated that FC supplementation, particularly at 3% (FC3 group), significantly improved body weight gain, feed intake, the survival rate, and the production efficiency index (PEI). The FC3 group exhibited optimal performance, potentially due to enhanced immune responses, as evidenced by higher IgA and IgG levels, and favorable cytokine regulation. Additionally, FC maintained intestinal epithelial integrity by upregulating tight junction proteins (ZO-1, Claudin-2) and reducing inflammatory responses (IFN-γ, TNF-α). Furthermore, FC3 demonstrated the ability to inhibit pathogenic bacteria (Salmonella spp., E. coli), promote beneficial Lactobacillus spp., and enhance intestinal mucosal morphology (villus height and crypt depth). These findings suggest that FC supplementation, particularly at 3%, is a promising natural alternative to antibiotics for controlling E. coli infections in broiler production.